Synthesis of cationic π-extended imidazolium salts by sequential Cu-catalyzed arylation/annulation and photocyclization. Issue 4 (15th December 2021) - Wang, Tianbao; Zheng, Qinze; Wang, Linhua; Huang, Zhenmei; Zhang, Huaxing; Zhang, Yuming; Zhang, Cheng; Gao, Ge
Abstract : Utilization of a sequential Cu-catalyzed arylation/annulation and photocyclization strategy, a series of cationic π-extended imidazolium salts were prepared. Abstract : A series of cationic π-extended imidazolium salts were synthesized by a sequential Cu-catalyzed arylation/annulation and photocyclization strategy in a simple but efficient way. Among them, a nine-fused-ring compound with a doubly aza[5]helical geometry is by far the largest cationic polycyclic heteroaromatic with a central imidazolium core.